Congregational health needs by key demographic variables: Findings from a congregational health needs assessment tool. (October 2022) - Harmon, Brook E.; San Diego, Emily Rose N.; Pichon, Latrice C.; Powell, Terrinieka W.; Rugless, Fedoria; West, Nathan T.; Minor, Lottie; McNeal, Sterling; McCann, Lauren; Hales, Lauren S.; Davis, Rachel; Lewis, Jonathan
Abstract: Health needs assessments identify important issues to be addressed and assist organizations in prioritizing resources. Using data from the Mid-South Congregational Health Survey, top health needs (physical, mental, social determinants of health) were identified, and differences in needs by key demographic variables (age, sex, race/ethnicity, education) were examined. Church leaders and members ( N  = 828) from 92 churches reported anxiety/depression (65 %), hypertension/stroke (65 %), stress (62 %), affordable healthcare (60 %), and overweight/obesity (58 %) as the top health needs in their congregations. Compared to individuals < 55 years old and with a college degree, individuals ≥ 55 years old (ORrange =1.50–1.86) and with ≤ high school degree (ORrange =1.55–1.91) were more likely to report mental health needs (anxiety/depression; stress). African Americans were less likely to report physical health needs (hypertension/stroke; overweight/obesity) than individuals categorized as Another race/ethnicity (ORrange =0.38–0.60). Individuals with ≤ high school degree were more likely to report affordable healthcare as a need compared to individuals with some college or a college degree (ORrange =1.58). This research highlights the need for evaluators and planners to design programs that are comprehensive in their approach to addressing the health needs of congregations while also considering demographic variation that may impact program participation and engagement. Highlights: Identified top health needs of congregations and communities they serve using a congregational health needs assessment. Examined differences in health needs by age, sex, race/ethnicity, and educational level. Provided direction for the development of holistic faith-based health promotion programs. Provided insight on how findings can be used to develop targeted programs and policies for congregations and the community.